Incidence and factors associated with postoperative nausea and vomiting at Debre Berhan referral hospital, NorthShewa, Ethiopia: Across-sectional study. (2020) - Allene, Mengesha Dessie; Demsie, Desalegn Getnet
Abstract: Background: Postoperative nausea and vomiting are the most common and disturbing complications following anaesthesia and surgery. Despite modern anaesthetic and surgical techniques, the incidence of postoperative nausea and vomiting remains high. This common complication is unpleasant for patients and delays recovery. Objective: The objective of this study was to determine the incidence of postoperative nausea and vomiting and associated factors. Method: A cross-sectional study was conducted from September 2 to December 27, 2019. A total of 398 patients who were operated on in this period were included in the study. Data were analysed by using SPSS version 22.0. Multivariable logistic regression was used to identify factors associated with postoperative nausea and vomiting. Result: The incidence of postoperative nausea, vomiting and nausea and vomiting were 79(19.85%), 16(4.02%) and 87(21.86%) respectively. Factors that were associated with postoperative nausea were female sex [AOR = 8.22; 95%CI = (5.31–17.51)], previous history of PONV [AOR = 7.32; 95%CI = (1.47–21.02)]; history of motion sickness [AOR = 3.64; 95%CI = (1.65–6.27)], duration of anesthesia >60 min [AOR = 3.21; 95%CI = (1.41–7.63)], use of postoperative opioids [AOR = 2.88; 95%CI = (1.91–18.95)] and obstetrics and gynaecology surgery [AOR = 6.20; 95%CI = (2.51–18.83)]. In addition, factors that were associated with postoperative vomiting were female sex [AOR = 6.88; 95%CI = (1.94–24.03)], previous history of PONV [AOR = 7.81; 95%CI= (1.21–18.46)], history of motion sickness [AOR = 5.00; 95%CI = (2.35–12.10)], duration of anesthesia >60 min [AOR = 2.87; 95%CI = (1.03–5.41)], use of postoperative opioids [AOR = 4.02; 95%CI=(1.34–12.01)] and obstetrics and gynaecology surgery [AOR = 7.32; 95% CI=(2.47–21.68)]. Conclusion and recommendations: The overall incidence of postoperative nausea and vomiting was higher compared with most studies conducted in the world. We recommend using of anti-emetic prophylaxis and formulation of postoperative nausea and vomiting treatment protocols. Highlights: Incidence of postoperative nausea, vomiting and nausea and vomiting were 19.85%, 4.02% and 21.86% respectively. In the current study, factors that cause nausea also cause vomiting. Patients should get anti-emetic prophylaxis.